COVID-19-induced Human Capital Shocks, Lifetime Labor Productivity, and Inequality - Michael Ralph M. Abrigo; Connie Bayudan-Dacuycuy; Aniceto C. Orbeta (Philippine Institute for Development Studies (PIDS), 2023)
Using a human capital model with stochastic lifetimes, we assess the potential long-term impacts of human capital spending shocks in the early years of the COVID-19 pandemic on survival, lifetime income, and inequality. In the model, health and education spending separately affect survival rates and potential labor productivity, respectively, which allows us to trace how the pandemic's effects may propagate through the economic lifecycle. We calibrate the model using recent National Transfer Account estimates for the Philippines. Simulation results suggest that the COVID-19 pandemic is likely to negatively affect health and labor productivity, thereby potentially worsening income inequality in the long run. These impacts appear to be more pronounced for some birth cohorts.
Keywords: 330; COVID-19; National Transfer Accounts; human capital